Naturwissenschaftliche Paradigmen und ethische Verantwortung: Ein kritischer Blick auf Stephen Toulmins »Kosmopolis« - Lohauß, Peter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1992)
Tue author agrees with Stephen Toulmin's demand for a 'recontextualization' of abstract principles of reason. Equipped with the authority of a deterministic world-view, they have influenced the politics and culture of the modern society to a !arge extent. A philosophy that insists on 'locality'and 'particularity' should, nevertheless, also take into account the actual problems of the contemporary societies, a task which Toulmin accomplishes only insufficiently.